Laboratory studies on performance of positive feed metering devices for band placement of fertilizers - Nathan, S K; Singh, B; Thakur, T C (Journal of Agricultural Engineering, 2000)
The effect of shape, number of grooves and speed of fluted roller metering device was studied on metering characteristics of urea for intermittent and continuous band placements. For intermittent band placement, 6 groove rollers of U-shape, J-shape and eccentric-circular shape were used whereas 12 groove rollers of U-shape and eccentric circular shape were selected for continuous band placement. The principle of two stage metering of fertilizer was employed using a star type agitator running at a constant speed of 0.26 m/s and a fixed circular opening of 13.5 mm diameter in the hopper at the first stage and varying speeds of 28,42,52,68 and 85 rpm for positive feed fluted rollers at the second stage. The results showed higher percentage deposition of urea in 100 mm bands with J-shape fluted roller followed by eccentric circular and U-shape fluted rollers. In case of continuous band placement, the coefficient of variation ranged from 20.11 to 11.17% with eccentric circular shape and 15.79 to 9.45% with U-shape fluted roller with increase in speed from 28 to 85 rpm.